Distinct nonlinear optical responses in three pairs of 2D homochiral Ag(i) enantiomers modulated by dicarboxylic acid ligands. Issue 2 (30th November 2021) - Gao, Congli; Zhou, Jianya; Cui, Minghui; Chen, Diming; Zhou, Liming; Li, Fengcai; Li, Xi-Li
Abstract : Based on three pairs of 2D homochiral Ag(i ) enantiomers, we demonstrate that both the symmetry and degree of π-conjugation of the ligands have a significant effect on the type and intensity of their NLO responses. Abstract : Three pairs of homochiral Ag(i ) enantiomers formulated as [Ag2 (LR )(pa)] n /[Ag2 (Ls )(pa)] n (R1 /S1, H2 pa = phthalic acid), [Ag2 (LR )(tda)] n ·H2 O/[Ag2 (Ls )(tda)] n ·H2 O (R2 /S2, H2 tda = 3, 4-thiophene dicarboxylic acid), and [Ag4 (LR )2 (3-npa)2 ] n /[Ag4 (Ls )2 (3-npa)2 ] n (R3 /S3, 3-H2 npa = 3-nitrophthalic acid) were prepared by using different dicarboxylic acid coligands via the reactions of AgNO3 with enantiopure monobidentate N-donor heterocyclic ligands named (+)/(−)-4, 5-pinenepyridyl-2-pyrazine (LS /LR ), respectively. Investigations on the nonlinear optical (NLO) response suggest R1 /S1 and R2 /S2 enantiomers present very strong third-harmonic generation (THG) responses, and the lowest THG intensities of R1 /S1 and R2 /S2 are 244 and 142 times that of α-SiO2, respectively. However, R3 /S3 enantiomers only exhibit mild second-harmonic generation (SHG) response (0.36 × KDP). A comparative study on the molecular structures of these Ag(i ) enantiomeric pairs reveals that both the symmetry and degree of π-conjugation of the dicarboxylate ligands are mainly responsible for their different NLO responses. Our research result not only provides a feasible method of constructing coordination polymers (CPs) with strong THG response but also points out an effective strategy for switching NLO behaviors from THG to SHG response.